Young people’s investments in sexual relationships: a different prioritization of self in the negotiation of safe sex practices in South Africa - van Der Riet, M; Sofika, D; Akhurst, J; Daniels, H (SAGE Publications, 2018)
In the South African context of high HIV prevalence, sexual relationships are entwined with risk. This qualitative study in a rural context examined how young people negotiate sexual practices and engage with this risk. Data was gathered from men and women (aged 15 to 33) in eight focus groups and 11 individual interviews. Abdication of self-care and deprioritization of self in the negotiation of safe sexual practices are reformulated into an understanding of the varied investments that young people make in particular kinds of sexual relationships. Sexual activity was found to underpin social reputation and identity production. In the trade-off between health protection and group membership, identity was related to investments in relationships that secured status for both genders. Future health-related interventions would need to work with other constructions of self in sexual relationships.